The Values of Moral Learning in âKetika Cinta Bertasbihâ Novel Written by Habiburrahman El Shirazy - Mulyadi, Mulyadi (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
A novel written by Habiburrahman El Shirazy âKetika Cinta Bertasbihâ (when love is connected to God) is decorated by a variety of ideas, values and ways of life. This novel does not only provide narrative story entertained with Islamic values, but also served as media to form public and readersâ morals. Because the story line presented in this novel contained an overview of everyday life containing of moral learning, therefore, it is very interesting to be studied. The current study seeks to uncover: 1) the value of moral learning and value of worship to Godâ 2) the value of self moral learning.Â The type of research is Library Research using discourse analysis method (content analysis).Â It was found out that (1) The moral value of learning to the God contained a message of faith with arguments through the universe.Â It let worship of God, be grateful and stay away from vanity. (2) The value of self-moral learning included the value patient, persevering, self-authority, high optimistic, responsibility and self-firm.